Development of Animalia Bio Board Game Media to Improve Students' Analytical Thinking and Collaboration Skills - Dea Merly Kirnasari; Evy Yulianti (Postgraduate, University of Mataram, 2025)
This study aims to determine the effectiveness of Bio Board Game (BBG) learning media on Animalia material to improve students' analytical thinking and collaboration skills. This development research was conducted using the ADDIE model. Product effectiveness analysis used MANOVA with a significance level of 0.05. The results of the Bio Board Game (BBG) learning media research have met the validity standards as a learning media reviewed from the aspects of design, learning, media use and visual communication and meet the practicality standards reviewed from the aspects of presentation, language, and visual communication. The results of the N-Gain test on analytical thinking skills were assessed as effective at 73.88 and collaboration skills received a fairly effective category with a value of 58.72, which means that the learning media is significant in improving students' collaboration skills.